Generic trade-offs and responses: an operations strategy analysis. (29th October 2004) - Slack, Nigel
Trade-off analysis is presented as a useful approach not only to conceptualising the process of operations performance improvement, but also to explain why certain trade-offs are chosen by companies. Two case studies are presented and subjected to similar analyses. The purpose of the paper is to identify three "generic" types of trade-off which need to be addressed by operations managers. Managers can then focus on the actions required to overcome these three types of trade-off over time. Furthermore, it will frame these improvement activities in terms of enhancing various aspects of operational flexibility. This is not a new idea. Previous studies have put forward flexibility as a key aspect of the "pivot" of any trade-off. Finally, the paper will discuss how organisations choose which trade-offs to tackle by examining the nature of the trade-offs themselves